The Kabbalistic Culture of Eighteenth-Century Prague : Ezekiel Landau (the 'Noda Biyehudah') and His Contemporaries. - Flatto, Sharon (Littman library of Jewish civilization (Series), 2015)
A comprehensive portrayal of rabbinic culture in eighteenth-century Prague highlighting the surprising centrality of kabbalah in one of the main centres of European Jewry.